2021
DOI: 10.1149/1945-7111/ac3a2a
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Material Activity and Selectivity in the Electrocatalytic Oxidation of Dibenzothiophene

Abstract: There is an increasing demand for efficient methods to remove sulfur from oil products, such as oxidative desulfurization. In this work, a set of five materials (gold, glassy carbon, nickel, palladium and platinum) were evaluated as electrochemical catalysts for the oxidation of dibenzothiophene (DBT). Bulk electrolysis performed without water present produced DBT dimer, while the addition of 2 M water produced dibenzothiophene sulfoxide (DBTO), both more polar than DBT. LC-MS and NMR were used to characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…Thierry et al studied the properties of several Fe-based films and observed the major Raman peak for ϒ-Fe2O3 to be between 650-740 cm -1 , stating also that a broad Raman band at 1425 cm -1 is characteristic of that film. 13 Finally, the transition from an oxyhydroxide to an oxide is also consistent with previously established behavior of a Fe film undergoing OER, where a progressively higher fraction of oxide phases (such as Fe2O3) relative to hydrated phases (such as FeOOH) was observed as oxidation occurred. 34 To investigate the electrocatalytic activity of the Fe film pre-and post-activation, Koutecky-Levich analysis was performed on a newly deposited Fe film, as well as on an Fe film which had undergone three hours of electrolysis.…”
Section: Catalytic Behavior Of the Iron Film For Dbto Productionsupporting
confidence: 89%
See 3 more Smart Citations
“…Thierry et al studied the properties of several Fe-based films and observed the major Raman peak for ϒ-Fe2O3 to be between 650-740 cm -1 , stating also that a broad Raman band at 1425 cm -1 is characteristic of that film. 13 Finally, the transition from an oxyhydroxide to an oxide is also consistent with previously established behavior of a Fe film undergoing OER, where a progressively higher fraction of oxide phases (such as Fe2O3) relative to hydrated phases (such as FeOOH) was observed as oxidation occurred. 34 To investigate the electrocatalytic activity of the Fe film pre-and post-activation, Koutecky-Levich analysis was performed on a newly deposited Fe film, as well as on an Fe film which had undergone three hours of electrolysis.…”
Section: Catalytic Behavior Of the Iron Film For Dbto Productionsupporting
confidence: 89%
“…For the Fe film electrodeposited on the Au RDE, cyclic voltammetry was first performed to establish whether it was capable of DBT oxidation. An oxidation peak was observed at 1.55 V vs SCE, which is in good agreement with the potential for DBT oxidation on other known electrocatalysts, 13 including Au (Figure S1). We next carried out bulk electrolysis of DBT using the Fe film.…”
Section: Catalytic Behavior Of the Iron Film For Dbto Productionsupporting
confidence: 84%
See 2 more Smart Citations
“…6 Typically, the oxidation is facilitated by a combination of a catalyst and a chemical oxidant. Herein, we focus on electrochemical ODS, 7 which has been shown to successfully remove up to 99.9% of sulfurcontaining compounds such as DBT, 8 and demonstrates a possibility of larger-scale applications in fuel processing. DBT is often used as a model sulfur-containing compound for ODS because it is poorly targeted by conventional desulfurization techniques.…”
Section: Introductionmentioning
confidence: 99%